Observations on the President's fiscal year 2003 federal science and technology budget (National Academy Press, 2002)
This study provides observations on the Administration's FY 2003 budget proposal for federal science and technology (FS & T) programs. The first section of the report outlines the development during the 1990s of national goals for science and technology (S & T), re-iterating the importance of U.S. leadership in these fields. It also comments on development of approach to tabulating and analyzing the federal S & T investment. The second section of the report summarizes the President's FY 2003 budget proposal, including proposals for spending on research for countering terrorism. The third section provides observations on the President's proposal, noting differences in funding trends by agency and outlining an approach to FS & T budgeting that focuses on both priority-driven and discovery-oriented research. The final section provides recommendations for ensuring that federally-funded S & T programs provide high-quality research outcomes that are relevant to agency missions and provide the U.S. with global leadership in S & T.